Screening of new bioactive materials from microbial extracts of soil microorganism (I) antimicrobial activity from 200 samples using microdilution assay - Jung, SO; Kim, J; Chang, IM; Ryu, JC (PHARMACEUTICAL SOCIETY KOREA, 1998)
The microdilution assay recommended by NCCLS (National Committee for Clinical Laboratory Standards) is one of the standardized methods of antibiotic susceptibility test. This method has been widely used clinically to obtain MIC values of antibiotics on pathogenic microorganisms. It is more convinient, rapid and simple to test many samples than other rest methods such as agar diffusion assay and broth macrodilution assay. The screening of antimicrobial agents from microbial extracts is too laborious in its process. Therefore, a number of screening methods having more simple procedure have been developed. In our laboratory, we applied microdilution assay for screening the antimicrobial agents. This assay showed dose-response results and was more sensitive than disc diffusion assay in our system. We tested 200 samples of microbial extracts originated from 100 microbial strains and selected several samples as potential candidates. In this report, we show that the microdilution assay is more convenient method in screeing of antibiotic susceptibility than those previously reported.